(untitled) (Economic and Political Thought, 2010)
Globalization is a real threat for the social market economy and globalization does not protect weak, ill and helpless people. Multinational corporations acknowledge only one criterion, i.e. profit. To illustrate the situation the author presents a short characteristic of international economic co-operation. He asks the following questions: What was the aim of deregulation of the economic markets? What chaos was caused by that deregulation? How can these negative tendencies be reversed? In conclusion the author speaks about the negative influence of globalization on the social market economy. He also describes the features of three attitudes towards globalization, i.e. a radical one, a neoliberal one and a reformist one. Globalization in its present version is spontaneous and will have to be “civilized” in the forthcoming decade.